A Numerical Model for the Interaction of Io‐Generated Alfvén Waves With Jupiter's Magnetosphere and Ionosphere. Issue 4 (24th April 2023) - Lysak, R. L.; Sulaiman, A. H.; Bagenal, F.; Crary, F.
Abstract: The interaction of Io with the corotating magnetosphere of Jupiter is known to produce Alfvén wings that couple the moon to Jupiter's ionosphere. We present first results from a new numerical model to describe the propagation of these Alfvén waves in this system. The model is cast in magnetic dipole coordinates and includes a dense plasma torus that is centered around the centrifugal equator. Results are presented for two density models, showing the dependence of the interaction on the magnetospheric density. Model results are presented for the case when Io is near the centrifugal and magnetic equators as well as when Io is at its northernmost magnetic latitude. The effect of the conductance of Jupiter's ionosphere is considered, showing that a long auroral footprint tail is favored by high Pedersen conductance in the ionosphere. The current patterns in these cases show a U‐shaped footprint due to the generation of field‐aligned current on the Jupiter‐facing and Jupiter‐opposed sides of Io, which may be related to the structure in the auroral footprint seen in the infrared by Juno. A model for the development of parallel electric fields is introduced, indicating that the main auroral footprints of Io can generate parallel potentials of up to 100 kV. Plain Language Summary: Jupiter's moon Io generates electrical currents when it passes through Jupiter's magnetic field. These currents take the form of fluctuations in the magnetic field lines, much like the waves on a stringed musical instrument. Due to the motion of Io, these waves follow behind Io and bounce back and forth between Jupiter and the dense ionized gas emitted by Io. This process creates auroral emissions that can be observed, e.g., with the Hubble Space Telescope. Key Points: The spacing of the main auroral spots in Io's footprint tail depends on the density profile assumed as well as the magnetic latitude of Io Partial reflections at the boundary of the Io plasma torus lead to secondary reflections and weaker auroral spots between the main spots The length of the auroral tail depends on the ionospheric conductance at Jupiter, with higher conductances leading to longer tails